Influence of Atlantic on the warming and reduction of sea ice in the Arctic - G. Alekseev V.; S. Kuzmina I.; N. Glok I.; A. Vyazilova E.; N. Ivanov E.; A. Smirnov V.; Г. Алексеев В.; С. Кузмина И.; Н. Глок И.; А. Вязилова Е.; Н. Иванов Е.; А. Смирнов В. (Ice and Snow, 2017)
Influence of anomalies of the sea surface temperature (SST) in low latitudes of the North Atlantic on the sea ice cover and the near-surface air temperature in the marine Arctic is discussed in the article. Data on the SST in the Atlantic Ocean from the HadISST dataset, climatic series of the water temperature at the section along the Kola meridian together with mean monthly data on the sea ice extent and the air surface temperature in the Maritime Arctic and the Northern hemisphere were analyzed. Multivariate cross-correlation analysis was applied to determine the maximum correlation coefficients between the SST anomalies, climate characteristics and their corresponding delays within time limits of 33 to 38 months. Existence of intimate link had been found between changes of the Atlantic SST in low latitudes and the sea ice extent in the Arctic with correlation coefficients up to 0.90 and delays up to 3 years. A mechanism of formation of the remote influence of low-latitude SST anomalies on the sea ice anomalies in the Arctic Ocean is proposed. The interpretation of this mechanism includes into consideration the interaction between atmospheric and oceanic circulation modes. Установлена связь между аномалиями температуры поверхности океана в приэкваториальной области Северной Атлантики и аномалиями приповерхностной температуры воздуха и площадью морского льда в Северном Ледовитом океане в разные месяцы. Механизм формирования удалённого влияния аномалий температуры поверхности океана на аномалии в Северном Ледовитом океане связан с системой взаимодействий между циркуляцией атмосферы и океана, переносящих тепло в высокие широты.